Penerapan Model Pembelajaran Kooperatif Tipe TGT Berbantuan Quizizz untuk Meningkatkan Hasil Belajar Matematika Siswa - Sartika, Mawar; Sukayasa, Sukayasa; Bakri M, Bakri M (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to improve student learning outcomes through the TGT type cooperative learning model assisted by Quizizz. This research was carried out as many as II cycles, by following the predetermined stages. This research method leads to the steps of classroom action research (PTK) with a qualitative approach. The results showed that from cycle I to cycle II showed an increase in student learning completeness in learning addition & subtraction operations for numbers using the TGT type cooperative learning model assisted by Quizizz, namely in cycle I by 40% and in cycle II by 78%. Given the determination of the success indicator has been achieved in cycle II with an average student score of 78%, learning mathematics using the TGT type cooperative learning model assisted by quizizz can be declared successful. Based on the results of the study, it can be concluded that the application of the Team Games Tournament (TGT) type cooperative learning model assisted by the quizizz application can improve students' mathematics learning outcomes. Keywords: Cooperative, Learning Outcomes, Quizizz, Tgt.